Can Inter-organizational Knowledge-Sharing Improve Enterprise Innovation Performance? The Mediator Effect of Innovation Capability and the Moderator Effect of Network Characteristics - Dongling, Wang; Yuming, Zhang; Xinmin, Liu; Chen, Jiakui; XiaoYi, Zhang; Chang, He (Frontiers in Communication, 2022)
This study investigates the relationship between inter-organizational knowledge-sharing and innovation performance based on the resource-based theory and network embedded theory. It aims to examine the mediating effect of network characteristics in the relationship between inter-organizational knowledge-sharing and innovation performance. Through quantitative study, data is collected from 275 firms and analyzed through regression analysis. The results reveal that inter-organizational knowledge-sharing has a positive effect on enterprise innovation capability. Innovation capability has a positive effect on enterprise innovation performance. The link between inter-organizational knowledge-sharing and innovation performance is mediated by enterprise innovation capability. Evidence in support of full mediation is found. Connection strength and network scale play a positive moderator role in the relationship between inter-organizational knowledge-sharing and innovation capability. The findings provide a theoretical basis for inter-organizational knowledge-sharing and help enterprises establish innovative advantages. These also guide the inter-organizational knowledge-sharing among members in practice.